« Amongst the Gods I Psyche will translate »: la réécriture par Thomas Shadwell de la tragédie-ballet Psyché (1671) de Molière, Corneille et Quinault - Pierre Degott (Revue LISA)
The present article aims at studying Thomas Shadwell’s adaptation of Molière, Corneille and Quinault’s tragédie-ballet of 1671, Psyché. A comparative examination of the two texts does indeed highlight the differing horizons of expectancy of the French and the English stages. If Shadwell’s play can be read as an allegory of the political situation of the Restoration, this article attempts to show that the English Psyche, boldly subtitled “The English Opera” by the musician Matthew Locke in his edition of the work, can also be seen as an allegorical representation of the operatic world itself. The third part of the article is therefore an examination of the various elements likely to support this interpretation.